Enhanced Power Generation Using Controlled Inoculum From Palm Oil Mill Effluent Fed Microbial Fuel Cell - Khan, Maksudur R.; Baranitharan, E.; Cheng, C. K.; Yousuf, Abu; Wee, Fei Aaron Teo; Tan, Geok Yuan Annie (Elsevier Ltd, 2015)

(untitled)
Enhancing the anode performance is a critical step for improving the power output of MFCs. This study 38 deals with the dual chamber MFCs to increase the power generation using the controlled inoculum in 39 Palm oil mill effluent (POME). Controlled inoculum (CI) was made using the predominant microorgan- 40 isms such as Pseudomonas aeruginosa, Azospira oryzae, Acetobacter peroxydans and Solimonas variicoloris 41 isolated from palm oil anaerobic sludge (AS) as well as from biofilm of MFC anode operated with AS 42 and identified using BIOLOG gene III analysis, PCR, DGGE and sequencing. Biofilm formation on electrode 43 was investigated by Fourier Transform Infrared spectroscopy (FTIR) and Thermogravimetric analayis 44(TGA). The MFC operated with Polyacrylonitrile carbon felt (PACF) anode and CI reached the maximum 45 power density of 107.35 mW/m 46 2, which was two times higher as compared to MFC operated with usual anaerobic sludge as inoculum. The maximum coulombic efficiency (CE) of 74% was achieved from the 47 MFC with CI, which was 50% higher than the CE with anaerobic sludge. But, it showed lower COD removal 48 efficiency of about 32%, which might be due to the absence of required fermentative microorganisms in CI 49 to utilize POME. The electrochemical activities have been investigated by electrochemical impedance 50 spectroscopy (EIS). EIS and the simulated results showed the significant reduction of charge transfer 51 resistance (Rct) by 40% during the operation of the cell with CI. EIS results provided evidence that there 52 was a substantial improvement in electron transfer between the microorganisms and the anode with CI. 53 These results demonstrate that the power output of MFCs can be increased significantly using CI.